Analysis Titanium Dioxide and Zinc Oxide in Physical Sunscreen Commercial with Protection Value 35 SPF - Sofaturrohman, Fuad; Rifka, Lia; Syalsabilla, Maritza; Syuriyani, Mira; Raisa, Nadia; Jonuarti, Riri; Ratnawulan, -; Hidayat, Rahmat (PILLAR OF PHYSICS, 2024)
This is descriptive research. A descriptive analysis method is a method of explaining symptoms using various variables from the study that are related to one another. This study investigated the shape, size, and composition of TiO2 and ZnO nanoparticles used in sunscreens to reflect and scatter ultraviolet radiation. The study focuses on the effects of these inorganic substances on ultraviolet and visible light absorption and reflection. XRF, UV-Vis spectroscopy, and XRD were used to analyze TiO2 and ZnO particles taken from 50-SPF sunscreen. The concentrations of TiO2 and ZnO in the product were 29.625% and 0.045%, respectively. The sizes of TiO2 and ZnO are obtained using a systematic equation, with the TiO2-particle nanosize of 26.31 nm in the form of TiO2-anorthic respectively. Based on the results obtained, the greater the TiO2 and ZnO content used, the greater the UV absorbance produced. Maximum absorbance indicates that electrons cannot absorb energy at that wavelength, so the energy is just passed through. Meanwhile, the greater the TiO2 and ZnO content used, the less reflectance there is in the UV region, and the visible light produced will also increase. Meanwhile, the greater the TiO2 and ZnO content used, the greater the reflectance in the UV region and the visible light produced